Residential solid waste is being a critical problem in many cities in clauding Jakarta. Cummnity-based management is the most important strategy even when sophiticated treatment such as bio-energy or waste industrial park word be implemented soon, as every waste processing neds separated wastes. Increasing the participation through community-based manajement is more effective than cange people’sperception and behavior on domestic wastes. In some cates, to change community behavior in waste se - Nonon Saribanon; Endriatmo Soetarto; Surjono H. Sutjahjo; E. Gumbira Sa’id; Sumardjo . (Forum Pasca Sarjana, 2009)
Residential solid waste is being a critical problem in many cities in clauding Jakarta.  Cummnity-based management is the most important strategy even when sophiticated treatment such as bio-energy or waste industrial park word be implemented soon, as every waste processing neds separated wastes.  Increasing the participation through community-based manajement is more effective than cange people’sperception and behavior on domestic wastes.  In some cates, to change community behavior in waste separition and recycling need more than ten years i.e. at Kampung Banjarsari, but with appropriate support system on sosial planning only took two years i.e. Kampung Rajawati.  The implementation constrain of this progammeis on replication or expandability of the progamme to implemented in another place.  There are also lack of government’s significantefforts to push and to supprots than action.  It’s true that some cummunities develop the some model, but without acceleration and exvandable progamme, the significance of that effort is very poor.  This study tried to ellaborate the model of system based ofnspatial analyses to determine resedential typology and found five resedential types i.e. high, middle-high, middle, middle-lower and lower level of resendential.  Quantitative analyses to determine typology of community participation found four types of cummnity participation i.e. moral-normative, moral-remunerayive, calculative-remuneraive and calculative-coercive.  Qualitative analyses had been ellaborated to determine authority or government policies typology.  Breaking down from these clssification, there strategies could develop, namely community participation strategy, infastructure development strategy and institutional manajement strategy.  Implementation of these models could accomodate the heterogeneity of communities and give positive impact on social acceptability.   Key words: social planning, community management, residential solid wastes